Kualitas ikan tongkol abu-abu (Thunnus tonggol) pada kondisi penyimpanan berbeda - Norita Norita; Mala Nurilmala; Asadatun Abdullah (Jurnal Pengolahan Hasil Perikanan Indonesia, 2019)
Low temperatures could inhibit bacteria producing histamine during fish handling process. Longtail tuna (Thunnus tonggol) is kept in ice starting from catching process until delivering to retail market to maintain quality of fish. However, long period of this storage causes growth of bacteria and deformation of histidine into histamine. This study was aimed to determine the effect of different storage conditions to the quality of longtail tuna through sensory and histamine test. Samples of longtail tuna were kept for 18 days in room temperature storage (28±2°C), cold temperature (0±3°C) and freezing temperature (-10±4°C). The quality of tuna was evaluated using Quality Index Method (QIM). The formation of histamine was analysed on day 0, 1, 2, 3, 4, 8, 14, 18 using spectrofluorometry method. Sensory acceptability limit at room temperature was one day, while cold storage reached 10 days with QIM score 11. Longtail tuna was spoiled on day 2 at room temperature with QIM score >12 and concentration of histamin at 1713.88 mg/kg. The results of histamine in frozen and cold storage on the 18th day were 59.99 mg/kg and 77.98 mg/kg, these results exceeded the FDA limit (50 mg/kg) but still below the limit of FAO (100 mg/kg).The best storage condition is frozen storage, maintaining sensory acceptability and preventing histamine formation.